Natural Killer (NK) Cell Functionality after human Spinal Cord Injury (SCI): protocol of a prospective, longitudinal study. Issue 1 (December 2016) - Laginha, Inês; Kopp, Marcel; Druschel, Claudia; Schaser, Klaus-Dieter; Brommer, Benedikt; Hellmann, Rick; Watzlawick, Ralf; Ossami-Saidi, Ramin-Raul; Prüss, Harald; Failli, Vieri; Meisel, Christian; Liebscher, Thomas; et al.
Abstract Background Natural killer (NK) cells comprise the main components of lymphocyte-mediated nonspecific immunity. Through their effector function they play a crucial role combating bacterial and viral challenges. They are also thought to be key contributors to the systemic spinal cord injury-induced immune-deficiency syndrome (SCI-IDS). SCI-IDS increases susceptibility to infection and extends to the post-acute and chronic phases after SCI. Methods and design The prospective study of NK cell function after traumatic SCI was carried out in two centers in Berlin, Germany. SCI patients and control patients with neurologically silent vertebral fracture also undergoing surgical stabilization were enrolled. Furthermore healthy controls were included to provide reference data. The NK cell function was assessed at 7 (5–9) days, 14 days (11–28) days, and 10 (8–12) weeks post-trauma. Clinical documentation included the American Spinal Injury Association (ASIA) impairment scale (AIS), neurological level of injury, infection status, concomitant injury, and medications. The primary endpoint of the study is CD107a expression by NK cells (cytotoxicity marker) 8–12 weeks following SCI. Secondary endpoints are the NK cell's TNF-α and IFN-γ production by the NK cells 8–12 weeks following SCI. Discussion The protocol of this study was developed to investigate the hypotheses whether i) SCI impairs NK cell function throughout the post-acute and sub-acute phases after SCI and ii) the degree of impairment relates to lesion height and severity. A deeper understanding of the SCI-IDS is crucial to enable strategies for prevention of infections, which are associated with poor neurological outcome and elevated mortality. Trial registration DRKS00009855 .